Perioperative management of pressure injury: a best practice implementation project. (30th September 2022) - Menšíková, Andrea; Klugarová, Jitka; Klugar, Miloslav; Menšík, Ivo; Soukopová, Žaneta; Pokorná, Andrea
ABSTRACT: Objectives: This project aimed to set up a control mechanism for the prevention of pressure injuries during surgery. Introduction: Structured and comprehensive risk assessment is effective in identifying individuals at risk for pressure injuries. The subsequent use of proper positioning aids (modern gel-filled positioning aids used to position the head and limbs: floating limb concept) reduces the incidence of surgery-related pressure injuries. Methods: The best practice implementation project used the JBI's Practical Application of Clinical Evidence System and Getting Research into Practice audit tool for promoting change in local healthcare practice. The study was carried out from January 2020 to February 2021 at the private clinic of aesthetic surgery (Brno, Czech Republic). A baseline audit involving 27 patients was undertaken and measured against six best practice recommendations. This step was followed by the implementation of targeted strategies and finally, a postimplementation follow-up audit was conducted. Results: The baseline audit results showed significant deficits between current practice and best practice in all but two criteria. Barriers to implementation of nursing clinical handover best practice criteria were identified by the project team and an education strategy was implemented, documentation for recording possible risks of pressure injuries was created, and new positioning aids were purchased and introduced into clinical practice. There were significantly improved outcomes across all best practice criteria in the follow-up audit. Conclusion: Clinical audits were proved to promote best practice in healthcare. Focused education, provision, and use of relevant tools and aids can have an immediate and positive impact on clinical practice. Future audits are planned to ensure the sustainability of practice changes.